The Mark of the Cognitive and the Coupling-Constitution Fallacy: A Defense of the Extended Mind Hypothesis - Piredda, Giulia (Frontiers in Psychology, 2017)
Clark and Chalmers (1998) introduced the extended mind hypothesis, according to which some mental states can be vehiculated by non-biological external resources. A lively debate has flourished around this hypothesis, connected with the issues of embodiment, embeddedness, situatedness and enaction (cf. Clark 2008, Menary 2010, Shapiro 2011). Two of the main criticisms addressed to the functionalist version of the extended mind thesis have been the so-called “coupling-constitution fallacy” and the alleged lack of a mark of the cognitive (Adams, Aizawa 2001, 2005, 2009, 2010a, 2010b). According to Adams and Aizawa, extended cognition is a logical possibility, but is not instantiated in our world. Following this view, they defend a “contingent intracranialism”, based on a specific mark of the cognitive that they propose. In this paper I intend to show that neither criticism is effective against the extended cognition thesis. In particular: • the mark of the cognitive proposed by Adams and Aizawa does not secure contingent intracranialism; • the coupling-constitution fallacy criticizes extended cognition on precisely the point the theory was intended to defend: namely, that the best way to individuate cognitive systems, given a minimal mark of the cognitive, is to rely on coupling relations between agents and environmental resources.